Migration and Mental Health: Evidence from a Natural Experiment - Stillman, Steven (2012)
People migrate to improve their well-being. Yet a large literature suggests that migration can be a stressful process, with potentially negative impacts on mental health. However, to truly understand the effect of migration one must compare the mental health of migrants to what their mental health would be had they stayed in their home country. The existing literature is not able to do this. New Zealand allows a quota of Tongans to immigrate each year with a random ballot used to choose amongst the excess number of applicants. Experimental estimates of the mental health effects of migration are obtained by comparing the mental health of migrants who were successful applicants in the random ballot to the mental health of those who applied to migrate under the quota, but whose names were not drawn. Migration is found to lead to improvements in mental health, particularly for women and those with poor mental health.